FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PERUSAHAAN DI BURSA EFEK INDONESIA - Pinatih, Ni Wayan Anindyanari Candranita; Sukartha, I Made (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
This study aimed to get empirical evidence of the company size, debt-equity ratio, profitability, subsidiaries,, the size of public accounting firm, audit fee, industry type, and auditor switching in audit delay. This research was conducted on all companies that were late to publish their annual financial report to the exchange in the period 2011-2015. The number of sampels taken are 75 companies with a purposive samping technique. The analysis technique used is multiple linear regression analysis. The result of this study show that , the size of public accounting firm and auditor switching have positive effect on audit delay, while  size of the company, debt-equity ratio, profitability, subsidiaries, audit fees, and industry types have no effect on audit delay.
Keywords: audit delay, company size, debt-equity ratio, profitability, subsidiaries